Dramatic Mode and the Feminist Poetics of Enactment in Daphne Marlatt’s Ana Historic - Waese, Rebecca (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2012)
Daphne Marlatt uses a dramatic mode in her fiction about history to circumvent patriarchal language and create a feminist poetics of enactment. Performative moments in Ana Historic enable the revisioning of historical moments, which are re-enacted in the mind’s eye of the protagonist. Exploring dramatic language, theatrical metaphors, and techniques of character building, Annie imagines a world outside of what is conventionally written about historical settler women and turns her focus on unwieldy female bodies – including the immigrant body, the hysterical body, the lesbian body, and the birthing body – to re-enact, rather than to document, a possible version of history. Theories of writing the body in text by Roland Barthes, Luce Irigaray, and others help illuminate Marlatt’s dramatic mode, which offers a way of exploring characters who have been neglected or restrained within traditional literary and historical representations – particularly female immigrants to nineteenth-century Canada – and supports a feminist writing strategy within and against language. Marlatt writes what she senses is her body’s language to signify beyond conventional systems of representation and to explore her characters’ interiors.